If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 20 = 3X + 120 Reorder the terms: 20 + 2X = 3X + 120 Reorder the terms: 20 + 2X = 120 + 3X Solving 20 + 2X = 120 + 3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3X' to each side of the equation. 20 + 2X + -3X = 120 + 3X + -3X Combine like terms: 2X + -3X = -1X 20 + -1X = 120 + 3X + -3X Combine like terms: 3X + -3X = 0 20 + -1X = 120 + 0 20 + -1X = 120 Add '-20' to each side of the equation. 20 + -20 + -1X = 120 + -20 Combine like terms: 20 + -20 = 0 0 + -1X = 120 + -20 -1X = 120 + -20 Combine like terms: 120 + -20 = 100 -1X = 100 Divide each side by '-1'. X = -100 Simplifying X = -100
| 6(w+5)= | | -3b-4=-4b-3b | | 75=30y+15 | | f(x)=.4x^5-2x^4+x^3-.5x+3 | | 4b+16a= | | 10x+11=3x-10 | | 21x-35=7y | | -16x^2+44x-24=0 | | 2x+51=7 | | 3+.4x=9y | | cos(2x)=.72 | | f(x)=2e^3x-1 | | 6x-12=5x-55-21 | | 4c-11+c=9 | | 2(2q+3)= | | t^2+6t+216=0 | | 14+15=7x+33 | | t^2+6a+216=0 | | 10x+60=12x | | (14/25)(-3/7)= | | 4(5u+1)= | | 6r-22=-47+r | | 14/25*(-3/7)= | | 224=90-x | | 5x=10-4y | | -3k+7+k=21 | | (7z+1)(3)= | | u+12=v | | 5.65x+16=31.9225+4x | | 1x-1y=1 | | 7x^2-1=-3x | | 32+100d=228 |